(untitled) - Braman, Sandra (Cambridge, Mass., 2006)
As the informational state replaces the bureaucratic welfare state, control over creation, processing, flows, and use has become the most effective form of power. In Change of State Sandra Braman examines the theoretical and practical ramifications of this "change of state." She looks at the ways in which governments are deliberate, explicit, and consistent in their use of information policy to exercise power, exploring not only such familiar topics as intellectual property rights and privacy but also areas in which policy is highly effective but little understood. Such lesser-known issues include hybrid citizenship, the use of "functionally equivalent borders" internally to allow exceptions to U.S. law, research funding, census methods, and network interconnection. Trends in information policy, argues Braman, both manifest and trigger change in the nature of governance itself." "Change of State introduces information policy on two levels, coupling discussions of specific contemporary problems with more abstract analysis drawing on social theory and empirical research as well as law. Most important, the book provides a way of understanding how information policy brings about the fundamental social changes that come with the transformation to the informational state
Keywords: Information policy,Chính sách thông tin; United States,Hoa Kỳ